PENGARUH LITERASI KEUANGAN TERHADAP PERENCANAAN KEUANGAN KELUARGA DI KOTA MATARAM - Dahlia Bonang (IQTISHADUNA, 2019)
Financial literacy and financial planning for every Indonesian family areimportant. It is because the family is one of the pillars of the economy where thefinancial health of the family will have an influence on the overall financial health ofthe country. If based on the province, NTB's financial literacy index is 17th in 34provinces in Indonesia at 21.45%. This figure indicates that there is still a low level ofunderstanding, knowledge and access of people in NTB to institutions, financialproducts, and services. Therefore financial education and supporting infrastructuredevelopment must be carried out continuously so that public financial literacy canreach well literate. This research is a field research. Data collection methods used areobservation, interviews and questionnaires. This study used a sample of 100 people.The sampling technique is by random sampling due to research efficiency. The output ofthe F test shows that the calculated F value is 4.516 with a significance level of 0.036.The significance level is 0.036 <0.05, so it can be interpreted that there is an influenceof financial literacy variable (X) on the family financial planning variable (Y).Similarly, it is proven by testing the second hypothesis with the T test. The output of theT test can be seen that the value of t count is 2.125. Then after t count compared to ttable which has a value of 1,980. With the value of t count 2.125> t table 1.980 it canbe concluded that Ho is accepted which means that "there is an influence of financialliteracy (X) on family financial planning (Y).